Clywed Cynghanedd - Cwrs Cerdd Dafod - Dafydd, Myrddin ap (Gwasg Carreg Gwalch, 2013)
A new edition of a course on the strict metre rules of Welsh poetry called cynghanedd based on an early 1990s radio series, with the main emphasis on enjoying playing with words. First published in 1994.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books